Allopurinol reduces antigen-specific and polyclonal activation of human T cells - Pérez-Mazliah, Damián; Albareda, María C.; Alvarez, María G.; Lococo, Bruno E.; Bertocchi, Graciela L.; Petti, Marcos; Viotti, Rodolfo; Laucella, Susana A. (Frontiers in Immunology, 2012)
Allopurinol is the most popular commercially available xanthine oxidase inhibitor and it is widely used for treatment of symptomatic hyperuricaemia, or gout. Although, several anti-inflammatory actions of allopurinol have been demonstrated in vivo and in vitro, there have been few studies on the action of allopurinol on T cells. In the current study, we have assessed the effect of allopurinol on antigen-specific and mitogen-driven activation and cytokine production in human T cells. Allopurinol markedly decreased the frequency of IFN-γ and IL-2-producing T cells, either after polyclonal or antigen-specific stimulation with Herpes Simplex virus 1, Influenza virus, tetanus toxoid and Trypanosoma cruzi-derived antigens. Allopurinol attenuated CD69 upregulation after CD3 and CD28 engagement and significantly reduced the levels of spontaneous and mitogen-induced intracellular reactive oxygen species in T cells. The diminished T cell activation and cytokine production in the presence of allopurinol support a direct action of allopurinol on human T cells, offering a potential pharmacological tool for the management of cell-mediated inflammatory diseases.